3D bioprinting of integral ADSCs-NO hydrogel scaffolds to promote severe burn wound healing. Issue 3 (25th April 2021) - Wu, Yu; Liang, Tangzhao; Hu, Ying; Jiang, Shihai; Luo, Yuansen; Liu, Chang; Wang, Guo; Zhang, Jing; Xu, Tao; Zhu, Lei
Abstract: Severe burns are challenging to heal and result in significant death throughout the world. Adipose-derived mesenchymal stem cells (ADSCs) have emerged as a promising treatment for full-thickness burn healing but are impeded by their low viability and efficiency after grafting in vivo . Nitric oxide (NO) is beneficial in promoting stem cell bioactivity, but whether it can function effectively in vivo is still largely unknown. In this study, we bioprinted an efficient biological scaffold loaded with ADSCs and NO (3D-ADSCs/NO) to evaluate its biological efficacy in promoting severe burn wound healing. The integral 3D-ADSCs/NO hydrogel scaffolds were constructed via 3D bioprinting. Our results shown that 3D-ADSCs/NO can enhance the migration and angiogenesis of Human Umbilical Vein Endothelial Cells (HUVECs). Burn wound healing experiments in mice revealed that 3D-ADSCs/NO accelerated the wound healing by promoting faster epithelialization and collagen deposition. Notably, immunohistochemistry of CD31 suggested an increase in neovascularization, supported by the upregulation of vascular endothelial growth factor (VEGF) mRNA in ADSCs in the 3D biosystem. These findings indicated that 3D-ADSC/NO hydrogel scaffold can promote severe burn wound healing through increased neovascularization via the VEGF signalling pathway. This scaffold may be considered a promising strategy for healing severe burns.